The Meaning of ‘Religion’ in Multicultural Societies Law (Stato, Chiese e pluralismo confessionale, 2017)
AA. VV. (Pierluigi Consorti, Giancarlo Anello e Mohamed A. ‘Arafa, Federica Botti, Rossella Bottoni, Cristina Dalla Villa, Maria d'Arienzo, Luigi Mariano Guzzo, Maria Luisa Lo Giacco, Adelaide Madera, Enrica Martinelli, Cristiana Maria Pettinato)
Keywords: Libertà di coscienza e di religione